Psychosocial factors affecting risk of post-partum depression among mothers and their Birth satisfaction: A systematic review - Mishra, Mineshi; Awasthi, Purnima (The Scientific Temper, 2025)
Negative birth experiences have been associated with an increased risk of post-partum depression (PPD). However, an exhaustive systematic literature review of existing literature examining this correlation is lacking. This systematic review investigates the association between birth satisfaction and the likelihood of post-partum depression. Additionally, it seeks to identify modifiable psychosocial factors influencing this relationship by conducting a systematic literature review of existing literature. Studies published between 2010 and 2024 were systematically reviewed, employing three electronic databases in compliance with PRISMA reporting guidelines. The inclusion criteria focused on studies conducting conceptual analysis on post-partum depression, birth satisfaction, or both. Search strategies utilized a wide range of terms, focusing on English-language publications. The systematic literature review was conducted in three phases: abstract review, title review, and full-text review. Twenty-one studies meeting the inclusion criteria were analyzed. A significant correlation was found between postnatal depression and birth dissatisfaction. Furthermore, psychosocial factors such as social support, maternal self-esteem, and healthcare facilities were identified as crucial factors influencing post-partum depression and birth satisfaction. These findings underscore the importance of tailored interventions to support maternal mental health during the post-partum period.